Does the addition of cognitive therapy to exposure and response prevention for obsessive compulsive disorder enhance clinical efficacy? A randomized controlled trial in a community setting. (8th July 2018) - Rector, Neil A.; Richter, Margaret A.; Katz, Danielle; Leybman, Michelle
Abstract : Objectives: Exposure and response prevention (ERP) remains the most empirically supported psychological treatment for obsessive compulsive disorder (OCD). Clinical guidelines recommend the addition of cognitive approaches to ERP although the presumed additive benefits have not been directly tested. The aim of this was to compare a treatment that integrated cognitive therapy with ERP (ERP + CT) to traditional, manualized ERP to test the additive benefits. Design: A longitudinal, randomized control trial design was used. Methods: Participants ( N  = 127) with OCD were randomly assigned to receive individual outpatient ERP or ERP + CT. Obsessive‐compulsive symptom severity measures were completed pre‐ and post‐treatment and at 6‐month follow‐up. Results: While both conditions led to significant symptom and obsessive belief reduction, ERP + CT led to significantly greater symptom and belief reduction as compared to ERP across all main symptom presentations of OCD. Based on a priori definitions of effectiveness, more patients in ERP + CT compared to the ERP group were also deemed treatment responders. Conclusions: The results of this study suggest that cognitive therapy can be readily integrated with ERP to improve clinical outcomes beyond ERP alone. Practitioner points: Both ERP and ERP + CT were effective, however a course of ERP + CT was significantly more effective at reducing symptoms of OCD than the ERP treatment condition. Significantly more participants who received ERP + CT experienced clinically significant change in OCD symptoms compared to those who received ERP. OCD symptom dimension did not significantly impact response to either ERP or ERP + CT treatments.